Impact of acculturation and psychological adjustment on mental health among migrant adolescents in Guangzhou, China: a cross-sectional questionnaire study. Issue 5 (5th May 2019) - Shi, Lishuo; Chen, Wen; Bouey, Jennifer Huang; Lin, Yanwei; Ling, Li
Abstract : Objectives: The aim of this study was to examine the pathway and associations among acculturation (ie, language, social interaction and lifestyle), psychological adjustment and mental health of internal migrant adolescents in China. Design: Cross-sectional questionnaire study. Setting: Six private migrant junior high schools located in Tianhe and Baiyun districts in Guangzhou were chosen as the study sites. Participants: A total of 1122 migrant adolescents aged 11–17 years old completed the study. Main outcome measures: Mental health was measured by using the Social Anxiety Scale for Children (SASC) and major depression disorder (MDD) in a Brief Child and Family Phone Interview. Acculturation and psychological adjustment were measured by a self-designed and verified questionnaire. Multiple regression models and structural equation models were performed to analyse the association among acculturation, psychological adjustment and mental health while controlling for participant demographic characteristics. Results: The average MDD score for boys was 8.78 (SD=2.17) and for girls was 8.56 (SD=2.22), while the average SASC score for boys was 14.67 (SD=3.72) and for girls was 13.41 (SD=4.01). Psychological adjustment had a direct positive effect on MDD (p<0.001, β=0.30) and SASC (p<0.001, β=0.28), and it was the key variable fully mediating the impact of acculturation components on MDD and partly mediating the impact of acculturation on SASC, whereas lifestyle showed a direct negative effect (p=0.003, β=−0.17) on SASC. Of the three acculturation components, lifestyle had the strongest influence on psychological adjustment (p<0.001, β=0.37 and 0.51), followed by social interaction (p<0.001, β=0.24 and 0.13) and language (p<0.001, β=0.17 and 0.11). Conclusions: The association between acculturation and the mental health of internal migrant adolescents was complex and could be mediated by psychological adjustment. Interventions such as promoting local language and social interaction are needed to enhance psychological adjustment and further improve the mental health of migrant adolescents.